The Influence of Using Twitter (X) To Enhance Critical Thinking Skill At Higher Education - Aura Paradiba; Dzul Rachman (Journal on Education, 2024)
This study aims to find out how Twitter can enhance students' critical thinking abilities in higher education, what factors influence it, and what way it is used to see if it improves critical thinking. This study examined the relationship between Twitter and critical thinking using mixed quantitative and qualitative method. This research was conducted in Universitas Muhammadiyah Kalimantan Timur, with the subject being the Twitter users of eighth semester and meet the criteria such as having a Twitter app and an account, using Twitter for more than a year, and have interacting with posts there. While multiple choice tests and questionnaires were used to collect quantitative data, interview was used to gather qualitative data. The results of the research showed that Twitter can help users develop their critical thinking skills with the ease of getting information and being a forum for effective discussion. Twitter is also a social media that is easy to access and has features that really help spread a wider perspective to help the learning process.